A randomized, placebo‐controlled proof‐of‐concept trial of adjunctive topiramate for alcohol use disorders in bipolar disorder. Issue 2 (19th February 2016) - Sylvia, Louisa G.; Gold, Alexandra K.; Stange, Jonathan P.; Peckham, Andrew D.; Deckersbach, Thilo; Calabrese, Joseph R.; Weiss, Roger D.; Perlis, Roy H.; Nierenberg, Andrew A.; Ostacher, Michael J.
Abstract : Background and Objectives: Topiramate is effective for alcohol use disorders (AUDs) among non‐psychiatric patients. We examined topiramate for treating comorbid AUDs in bipolar disorder (BD). Methods: Twelve participants were randomized to topiramate or placebo for 12 weeks. Results: The topiramate group, with two out of five participants (40%) completing treatment, experienced less improvement in drinking patterns than the placebo group, with five out of seven participants (71%) completing treatment. Discussion and Conclusions: Topiramate did not improve drinking behavior and was not well‐tolerated. This study failed to recruit adequately. Problems surrounding high attrition, a small study sample, and missing data preclude interpretation of study findings. Scientific Significance: This is the first randomized, placebo‐controlled trial of topiramate for AUDs in BD. (Am J Addict 2016;25:94–98)